2021
DOI: 10.3389/fmicb.2021.764178
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Aerobiology

Abstract: Ocean aerobiology is defined here as the study of biological particles of marine origin, including living organisms, present in the atmosphere and their role in ecological, biogeochemical, and climate processes. Hundreds of trillions of microorganisms are exchanged between ocean and atmosphere daily. Within a few days, tropospheric transport potentially disperses microorganisms over continents and between oceans. There is a need to better identify and quantify marine aerobiota, characterize the time spans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 301 publications
(435 reference statements)
0
16
0
Order By: Relevance
“…Almost 90% of storms form within 20° north or south of the equator (Britannica, 2022;National Hurricane Center and Central Paci c Hurricane Center National Oceanic and Atmospheric Administration, 2022), and CBM is also endemic in this region (Queiroz-Telles et al, 2017;Santos et al, 2021). Notably, the ndings of DeLeon-Rodriguez et al, (2013) (DeLeon-Rodriguez et al, 2013 suggested that fogging of large fungal spore communities occurs during tropical hurricanes, and airborne fungi may remain viable after being carried aloft (Alsante et al, 2021;Mayer et al, 2020), where long-distance, transcontinental and even oceanic transport occurs. The fungal microbiota is a dynamic and underappreciated aspect of the lower oceanic layer, and the extensive ooding after mega-hurricanes can create ideal conditions (Barbeau et al, 2010) for the growth of molds such as Fonsecaea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 90% of storms form within 20° north or south of the equator (Britannica, 2022;National Hurricane Center and Central Paci c Hurricane Center National Oceanic and Atmospheric Administration, 2022), and CBM is also endemic in this region (Queiroz-Telles et al, 2017;Santos et al, 2021). Notably, the ndings of DeLeon-Rodriguez et al, (2013) (DeLeon-Rodriguez et al, 2013 suggested that fogging of large fungal spore communities occurs during tropical hurricanes, and airborne fungi may remain viable after being carried aloft (Alsante et al, 2021;Mayer et al, 2020), where long-distance, transcontinental and even oceanic transport occurs. The fungal microbiota is a dynamic and underappreciated aspect of the lower oceanic layer, and the extensive ooding after mega-hurricanes can create ideal conditions (Barbeau et al, 2010) for the growth of molds such as Fonsecaea spp.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we cannot state which bacterial phylotypes remained viable during atmospheric transport and were actively growing or involved in specific cellular pathways. This question could be investigated by sequencing efforts of the airborne ribosomal 16S RNA transcripts as well as other specific genes of interest (Alsante et al, 2021). One such gene could be nifH as airborne diazotrophs are routinely found in dust samples (Foster et al, 2009), which, in turn, may fix N 2 upon deposition in seawater (Rahav et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The low levels of the relatively viability proxy during the dust event may be attributed to anthropogenic inhibitors carried by the dust, mainly metals and organic pollutants. Thus, transport time, the presence of pollutants and the chemical reactions on surface particles during the dust event probably impacted the microbial viability, yet further research is needed to assess how physical and chemical microhabitats impacts microorganism functionality (Alsante et al, 2021). Moreover, given the acidic conditions in the atmosphere and clouds (Pye et al, 2020), trace-metals leachability and thus potential toxicity may increase (Koçak et al, 2007).…”
Section: Viability Proxy Of Airborne Prokaryotes During An Extreme Du...mentioning
confidence: 99%
See 1 more Smart Citation
“…Virus aerosolization from the SML was previously studied 15,30,33 , but investigations pursuing metagenomic approaches to explore the virioneuston and its aerosolization in the field are lacking. A recent review highlighted the need to quantify marine aerobiota, to characterize the spatial-temporal dimensions of dispersal, and to understand acclimations of marine microorganisms to atmospheric conditions 34 . Once airborne, viruses could even fulfill other functions as recently suggested 35 : Airborne marine viruses could serve as ice-nucleating particles (INP), a function already described for many microorganisms 36,37 , and act as catalysts to mediate freezing at temperatures warmer than - 10 °C.…”
mentioning
confidence: 99%